Psychiatry : breaking the ICE : introductions, common tasks, emergencies for trainees - Stringer, Sarah; Hurn, Juliet; Husain, Mujtaba (Wiley Blackwell, 2015)
Psychiatry: Breaking the ICE contains everything psychiatry trainees need in order feel confident and competent in general adult inpatient and community placements.-A practical and reassuring guide to life as a psychiatrist, structured around the tasks expected both in day-to-day practice and in out-of-hours work -Key themes running throughout the book include ethical and legal issues, risk assessment and management, patient experience and safe prescribing -The authors are closely involved in the training, mentoring and supervision of core trainees, and know the real-world challenges faced by junior psychiatrists.